SlORFfinder: a tool to detect open reading frames resulting from trans-splicing of spliced leader sequences. Issue 1 (5th January 2023) - Song, Bo; Li, Hao; Jiang, Mengyun; Gao, Zhongtian; Wang, Suikang; Gao, Lei; Chen, Yunsheng; Li, Wujiao
Abstract: Trans -splicing of a spliced leader (SL) to the 5′ ends of mRNAs is used to produce mature mRNAs in several phyla of great importance to human health and the marine ecosystem. One of the consequences of the addition of SL sequences is the change or disruption of the open reading frames (ORFs) in the recipient transcripts. Given that most SL sequences have one or more of the trinucleotide NUG, including AUG in flatworms, trans -splicing of SL sequences can potentially supply a start codon to create new ORFs, which we refer to as slORFs, in the recipient mRNAs. Due to the lack of a tool to precisely detect them, slORFs were usually neglected in previous studies. In this work, we present the tool slORFfinder, which automatically links the SL sequences to the recipient mRNAs at the trans -splicing sites identified from SL-containing reads of RNA-Seq and predicts slORFs according to the distribution of ribosome-protected footprints (RPFs) on the trans -spliced transcripts. By applying this tool to the analyses of nematodes, ascidians and euglena, whose RPFs are publicly available, we find wide existence of slORFs in these taxa. Furthermore, we find that slORFs are generally translated at higher levels than the annotated ORFs in the genomes, suggesting they might have important functions. Overall, this study provides a tool, slORFfinder (https://github.com/songbo446/slORFfinder ), to identify slORFs, which can enhance our understanding of ORFs in taxa with SL machinery.